A solution-processed high performance organic solar cell using a small molecule with the thieno[3, 2-b]thiophene central unit. Issue 83 (2nd September 2015) - Zhang, Qian; Wang, Yunchuang; Kan, Bin; Wan, Xiangjian; Liu, Feng; Ni, Wang; Feng, Huanran; Russell, Thomas P.; Chen, Yongsheng
Abstract : Replacing the double thiophene unit ofDRCN8T with thieno[3, 2- b ]thiophene, DRCN8TT a high efficiency of 8.11% was achieved, benefiting from the more preferred morphology. Abstract : A solution processed acceptor–donor–acceptor (A–D–A) small molecule with thieno[3, 2- b ]thiophene as the central building block and 2-(1, 1-dicyanomethylene)-rhodanine as the terminal unit, DRCN8TT, was designed and synthesized. The optimized power conversion efficiency (PCE) of 8.11% was achieved, which is much higher than that of its analogue moleculeDRCN8T . The improved performance was ascribed to the morphology which consisted of small, highly crystalline domains that were nearly commensurate with the exiton diffusion length.